89.5k views
0 votes
Find the inverse of g(x) = 3x^2 - 5

User Moseph
by
4.8k points

1 Answer

6 votes

Answer:

g
^(-1)(x)= √((x-5)/3)

Explanation:

g(x) is the domain so it can be written as y as g(x) changes with the value of x.

Basically to find the inverse, replace the function(x) with y and then make x the subject.

y= 3x^2-5

y-5=3x^2

x^2= (y-5)/3

x= √((y-5)/3)

Do not leave the answer like this replace the y with x like the following

g
^(-1)(x)= √((x-5)/3)

User Lovey
by
6.1k points